The Law of the Sea and the Caracas Conference - Bustamante y Rivero, José Luis (1974)
During the 1970s, the United Nations convened several conferences focused on deliberating the Law of the Sea. The primary aim of these gatherings was to reassess and modernize the outdated maritime legal framework while establishing new mechanisms for social governance in marine environments. This paper seeks to analyze the proposed new legal framework for oceanic space management while also articulating a series of critiques regarding these proposed modifications.